الإعلام السياحي و أثره علىصورة السياحة الداخلية في الجزائر -دراسة ميدانية لعينة من السياح- (مجلة الواحات للبحوث والدراسات, 2015)
Domestictourismis one of the economicactivities of crucial importance in today's world, many countries are based on thisphenomenon in theireconomies for the benefitstheyreceive, first for the exploitation of labor, and large incomeobtained. As wellTourist media are considered as one of the main axes in progress of the sector, through the roleitcouldpotentiallyplay in the formation of positive image and installingit in tourists' mindaccording to the differentavailable media. This research deals with the impact of the tourist media on the image of domestictourism and consists of different important aspects such as: the conceptualframework of Domestictourism image and tourist media, thusdetermines the impact of the tourist media on the image through an investigation among a group of tourists in the east of algeria.Key words :Tourist media, the image of domestictourism, components of image.